2013
DOI: 10.1016/j.jpeds.2013.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nutritional Rehabilitation on Gastric Motility and Somatization in Adolescents with Anorexia

Abstract: Objective To examine gastric function, as well as the presence of somatic complaints, anxiety symptoms, and functional gastrointestinal disorders (FGIDs), in adolescents with anorexia nervosa (AN) before and after nutritional rehabilitation. Study design Sixteen females with AN and 22 healthy controls with similar demographic profiles were included. Gastric emptying (measured as residual gastric volume) and gastric accommodation (measured as postprandial antral diameter) were assessed with abdominal ultrason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 52 publications
(48 reference statements)
3
68
0
1
Order By: Relevance
“…These findings are consistent with previous studies that often reported delayed gastric emptying for AN, but similar emptying in OB compared to HC [1619, 25, 2731, 50–52]. Interestingly, no difference in antral contraction frequency was present between groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with previous studies that often reported delayed gastric emptying for AN, but similar emptying in OB compared to HC [1619, 25, 2731, 50–52]. Interestingly, no difference in antral contraction frequency was present between groups.…”
Section: Discussionsupporting
confidence: 92%
“…It should be noted that AN2 patients were still underweight (average BMI of 18.1 kg/m 2 ) and that this effect might have been more distinct with more pronounced increase in BMI. This finding is consistent with previous studies in AN with comparable follow-up time and BMI at follow-up [25, 27, 29, 50, 72]. These investigations found accelerated gastric emptying particularly in the restrictive type of anorexia nervosa, while gastric emptying in the purging type remained unchanged (here 9 of 12 patients that gained weight were classified as restrictive type AN at study entry).…”
Section: Discussionsupporting
confidence: 92%
“…Boyd, Abraham, and Kellow () and Boyd, Abraham, and Kellow () studies have found that 97–98% of inpatients with an ED had a gastrointestinal disorder, 53% had three or more gastrointestinal disorders, and 77% continued to have a gastrointestinal disorder at 12‐month follow‐up (Boyd et al, ). Children with AN specifically have a high rate of gastrointestinal disorders or symptoms (75–79%) compared to healthy children and the severity of AN is positively associated with gastrointestinal symptoms (Lee, Ng, Kwok, Thomas, & Becker, ; Perez, Coley, Crandall, Di Lorenzo, & Bravender, ). Irritable bowel syndrome presents as the most common gastrointestinal disorder in children with AN (Perez et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…This measure of anxiety symptoms has well-established psychometric properties, 24 and has been used with children and adolescents with chronic illnesses. 25 …”
Section: Methodsmentioning
confidence: 99%